2015
DOI: 10.1159/000431380
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pulmonary Hypertension Associated with COPD: Hemodynamic Improvement with Specific Therapy

Abstract: Background: There is no recommendation for treating pulmonary hypertension (PH) when associated with chronic obstructive pulmonary disease (COPD). Objective: To evaluate the effect of PH-specific therapy in patients with COPD. Methods: All successive patients with severe PH [mean pulmonary arterial pressure (mPAP) ≥35 mm Hg] and COPD, who received specific PH medication and who underwent right heart catheterization at baseline and after 3-12 months of treatment, were analyzed from a prospective database. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…Despite the absence of a validated indication, some non-PAH patients in our cohort received an off-label PAH-targeted therapy. This trend has also been found in other cohort studies, like the ASPIRE registry [23] or others [32,33,34]. However, it is now clearly stated in the 2015 ESC/ERS guidelines [7] that PAH treatment is not recommended in patients with PH from another group than 1, and now 4 for riociguat.…”
Section: Discussionsupporting
confidence: 64%
“…Despite the absence of a validated indication, some non-PAH patients in our cohort received an off-label PAH-targeted therapy. This trend has also been found in other cohort studies, like the ASPIRE registry [23] or others [32,33,34]. However, it is now clearly stated in the 2015 ESC/ERS guidelines [7] that PAH treatment is not recommended in patients with PH from another group than 1, and now 4 for riociguat.…”
Section: Discussionsupporting
confidence: 64%
“…There are few studies in the literature which evaluated the hemodynamic status of PH-COPD in patients treated with specific PH therapy, and the results are contradictory [10,13,18,19,20,21]. A recent meta-analysis which included 9 randomized controlled trials concerning PH-specific therapy in PH-COPD patients showed an improvement in dyspnea, exercise capacity, and PAP [22].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the exact mechanism of sildenafil or other phosphodiesterase-5 (PDE-5) inhibitors on dyspnea status of patients with COPD has not been well demonstrated [21,22]. However, its role in amelioration of dyspnea status in patients with other cardio-respiratory diseases has been described by previous studies [23,24].…”
Section: Discussionmentioning
confidence: 99%